Good and Bad Hair - Gaskins, Bill, 1953- (Book collections on Project MUSE., 1997)
"Features sixty evocative photographs of African-American men, women, and children, documenting contemporary Black hairstyles and their role as a feature of African-American culture."--Jacket.